2004
DOI: 10.6004/jnccn.2004.0050
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Based Cytology: Evaluation of Effectiveness, Cost-Effectiveness, and Application to Present Practice

Abstract: This article reviews the data available as of 2004 on the effectiveness and cost-effectiveness of cervical screening with the two available cytologic methods, the conventional Papanicolaou (Pap; CP) smear and liquid-based cytology (LBC), and discusses the application of LBC to current practice. The majority of LBC studies are on the ThinPrep Pap Test (CYTYC, Boxsborough, MA) and the remainder are on SurePath (TriPath, Burlington, NC), which was previously known as AutoCyte Prep. LBC identified more low-grade s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 54 publications
0
39
0
2
Order By: Relevance
“…[8910] Few researchers have applied LBC technology to BW/lavage specimens and only limited data on its utility is available in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…[8910] Few researchers have applied LBC technology to BW/lavage specimens and only limited data on its utility is available in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Results on the cost-effectiveness of LBC are conflicting, depending on whether studies found improvements in the adequacy or detection of abnormality rates. A study by Taylor et al 20 found that a commonly used LBC product reduced the number of inadequate smears but did not improve detection of histology-confirmed disease (cervical intraepithelial neoplasia grade 1 or worse) and therefore concluded that the increased cost does not justify the implementation of LBC. In contrast, a review by Cox 21 showed that LBC was cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, multiple studies have noted the strong positive association between cytologic screening and histologic diagnosis in detecting cervical dysplasia. 13,14,125 There was a significant association between cytology and histology (p = .019) among women who had no progesterone exposure (Table 4-3). This again would be expected, based on what is known in the literature.…”
Section: Relationship Between Cytology and Histology According To Promentioning
confidence: 99%
“…The ASCUS/LSIL Triage study (or "ALTS," as it is referred to) of 1995-2001 set the standard for much of what is known about the relationship between abnormal cytology and subsequent histology. 13 Treatment of cervical dysplasia and neoplasia is determined by the histology result, thus clinicians and researchers must understand the relationship between cytology and histology. Further, factors that may affect that relationship need to be well understood.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation